2012
DOI: 10.1166/jnn.2012.6626
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanocrystals Mediated Combination Therapy of Radiation with Magnetic Hyperthermia on Glioma Cells

Abstract: Based on the study of apoptosis-induced and anti-proliferation behavior of silver nanoparticles (AgNPs) on cancer cells, the attractively therapeutic effect and potential application of AgNPs in anti-cancer field was gradually revealed. Here we investigated the effect of 10 nm silver nanoparticles (AgNPs) on human glioma U251 cells upon the combination treatment of ionizing radiation (IR) treatment with magnetic hyperthermia (MHT). AgNPs showed both radio and thermo sensitivity on U251 cells from the surviving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 35 publications
(38 reference statements)
1
19
0
Order By: Relevance
“…68 Jiang et al reported that cellular uptake of AgNPs of #20 nm was greater than that of AgNPs of .100 nm in human glioma U251 cells. 69 Our results are consistent with those previously reported. For example, Park et al showed the effects of various sizes of AgNPs (20, 80, and 113 nm) using in vitro assays for cytotoxicity, inflammation, genotoxicity, and developmental toxicity, and finally concluded that AgNPs of 20 nm were more toxic than larger nanoparticles.…”
Section: Cytotoxicity Of B-agnps and F-agnpssupporting
confidence: 94%
“…68 Jiang et al reported that cellular uptake of AgNPs of #20 nm was greater than that of AgNPs of .100 nm in human glioma U251 cells. 69 Our results are consistent with those previously reported. For example, Park et al showed the effects of various sizes of AgNPs (20, 80, and 113 nm) using in vitro assays for cytotoxicity, inflammation, genotoxicity, and developmental toxicity, and finally concluded that AgNPs of 20 nm were more toxic than larger nanoparticles.…”
Section: Cytotoxicity Of B-agnps and F-agnpssupporting
confidence: 94%
“…Combination of MHT with chemotherapy and/or RT has already been studied to a limited extent [106,107]. Phase I and II studies of MHT in combination with RT have been performed in patients with recurrent GBM (see below).…”
Section: Magnetic Hyperthermia Therapymentioning
confidence: 99%
“…In another study, U251 human glioma cells were initially treated in vitro with silver nanocrystals (AgNPs), maghemite MNPs or a combination of both, followed by RT and AMF treatment [107]. All treatment groups received 0–6 Gy of RT and were then exposed to an AMF for 15 min.…”
Section: Magnetic Hyperthermia Therapymentioning
confidence: 99%
“…As intracellular AgNPs accumulated, the apoptosis rate of U251 cells was enhanced. Furthermore, AgNPs significantly inhibited cancer cell proliferation when combined with hyperthermic conditions [ 187 ]. The combination of AgNPs and DOX could form stable complexes that strongly interacted with DNA.…”
Section: Types Of Nps Used For Combination Therapymentioning
confidence: 99%